2017
DOI: 10.1186/s12985-017-0736-2
|View full text |Cite
|
Sign up to set email alerts
|

HPV16-E2 protein modifies self-renewal and differentiation rate in progenitor cells of human immortalized keratinocytes

Abstract: BackgroundCervical cancer is the fourth cause of death worldwide by cancer in women and is a disease associated to persistent infection with human papillomavirus (HPV), particularly from two high-risk types HPV16 and 18. The virus initiates its replicative cycle infecting cells located in the basal layer of the epithelium, where a small population of epithelial stem cells is located performing important functions of renewal and maintenance of the tissue. Viral E2 gene is one of the first expressed after infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…CC is a common gynecological tumor that threatens women’s health. CSCs are characterized by self-renewal, multi-directional differentiation, radiotherapy and chemotherapy resistance, high tumorigenicity and so on, and may affect the invasion, metastasis, and recurrence of CC [30–32].…”
Section: Discussionmentioning
confidence: 99%
“…CC is a common gynecological tumor that threatens women’s health. CSCs are characterized by self-renewal, multi-directional differentiation, radiotherapy and chemotherapy resistance, high tumorigenicity and so on, and may affect the invasion, metastasis, and recurrence of CC [30–32].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some reports have indicated that CD71 À or CD71 dim populations also display stem cell characteristics in some cancers. Elevated expression of "stemness" genes was detected in a side population (a6-integrin bri /CD71 dim ) isolated from spontaneously immortalized keratinocytes in the HaCaT cell line that showed epithelial progenitor cell characteristics (25). Furthermore, an enriched CD71 À subpopulation was found in the gastric adenosquamous carcinoma cell line MKN-1 after 5-fluorouracil treatment, and the CD71 À subpopulation exhibited elevated migratory and invasive ability, enhanced selfrenewal ability, and tumorigenicity (26).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, CC is the second most common cause of cancer-associated mortality in women (2018), primarily due to poor clinical diagnosis during the early stages of disease (7,10). Previous reports between 2015 and 2017 revealed that HPV-16 and HPV-18 are responsible for 65–75% of precancerous cervical lesions and are present in 99% of patients with CC worldwide (9,1113). However, it has also been established that HPV infections do not necessarily trigger CC (9,12,13).…”
Section: Overviewmentioning
confidence: 99%
“…Although a number of genetic and molecular events require further clarification in cervical carcinogenesis, it is currently accepted that HPV viruses depend on epithelial cell differentiation to establish their progeny and spread their viral genes (1113). HPV has a more significant opportunity to infect basal cells with stem cell-like properties and integrate its viral DNA into the genome of these cells, driving the oncogenic transformation into CCSCs (13,23).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation